2021
DOI: 10.1038/s41380-021-01161-7
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset of mental disorders worldwide: large-scale meta-analysis of 192 epidemiological studies

Abstract: Promotion of good mental health, prevention, and early intervention before/at the onset of mental disorders improve outcomes. However, the range and peak ages at onset for mental disorders are not fully established. To provide robust, global epidemiological estimates of age at onset for mental disorders, we conducted a PRISMA/MOOSE-compliant systematic review with meta-analysis of birth cohort/cross-sectional/cohort studies, representative of the general population, reporting age at onset for any ICD/DSM-menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
830
5
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 1,717 publications
(1,099 citation statements)
references
References 63 publications
27
830
5
9
Order By: Relevance
“…Earlier onset is often associated with a poorer outcome [37]. Promotion of good mental health, prevention, and early intervention before/at the onset of mental disorders improve outcomes [38]. We could speculate that our findings could be potentially useful for families with psychiatric burden when they pass prenatal genetic counseling for psychiatric disorders, although our data need to be confirmed on a larger sample.…”
Section: Discussionmentioning
confidence: 74%
“…Earlier onset is often associated with a poorer outcome [37]. Promotion of good mental health, prevention, and early intervention before/at the onset of mental disorders improve outcomes [38]. We could speculate that our findings could be potentially useful for families with psychiatric burden when they pass prenatal genetic counseling for psychiatric disorders, although our data need to be confirmed on a larger sample.…”
Section: Discussionmentioning
confidence: 74%
“…All ITAPP centers were targeting a transitional age (12-39 years), with minor variations across sites. This is relevant, because a large-scale meta-analysis found that 12.3% of psychotic disorders occur before the age of 18 and 47.8% before 25, with a peak onset at 20.5 years [28]. These findings do not support the current pediatric-adult bifurcation of mental health services (cut at the age of 15 or 18) in Italy, where young people may fall into institutional gaps when they are most liable to mental disorders [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous early-pandemic studies have reported high levels of adolescent psychopathology and anxiety symptoms (e.g., Luijten et al, 2021;Waite et al, 2021). However, since many of these studies have no pre-COVID-19 data, their results may reflect the moderate to high levels of adolescent psychopathology already present in adolescent populations before the pandemic (e.g., Kessler et al, 2005;Solmi et al, 2021). Where studies have been able to combine pre-and early-pandemic data on psychopathology symptoms, results are limited and conflicting.…”
Section: Decrease In Anxiety Symptoms and Less Overall Symptoms Than Expectedmentioning
confidence: 99%